THE EFFECT OF PERINEAL LACERATIONS IN DEVELOPMENT OF POSTPARTUM DEPRESSION - Ni Putu Yunita Sri Lestari; Ratri Istiqomah (Journal of Psychiatry Psychology and Behavioral Research, 2022)
Spontaneous vaginal deliveries allows perineal lacerations. The level of resistance of a person to perineal lacerations varies widely. The risk of developing postpartum depression is experienced by different groups of women. In the early months after delivery, depression is the most common morbidity in postpartum women. The presence of perineal lacerations can be a factor in the development of postpartum depression. Stress and anxiety disorders can be caused by the occurrence of grade 3 and 4 perineal lacerations. This study looked at the potential effect of perineal laceration on the incidence of postpartum depression in women with vaginal delivery. This systematic review used study research that related to postpartum depression and perineal lacerations. Articles that are relevant are searched for by the author on Google Scholar, ScienceDirect, and Pubmed from the last 5 years (2015-2020). By 5 of the 77 studies were discussed in the review. The studies were conducted in United States, Taiwan, France, Brazil, and Sweden, total 4.966 women were included. Three of five studies showing that the presence of perineal lacerations increases the incidence of postpartum depression but along with the development, two research from the last 2 years, perineal lacerations did not increase risk of postpartum depression. However, severe perineal lacerations increase risk of postpartum depression among women with low resilience with 3rd- 4th degree of perineal laceration support development of postnatal depression in women.Keywords: perineal, lacerations, depression, postpartum.